Mapping Research Trends in Global Climate Change Adaptation to Flood Disasters: A Bibliometric Analysis using VOSviewer - Pahleviannur, Muhammad Rizal (Innovative Technologica: Methodical Research Journal, 2024)
Using a bibliometric analysis, this study aims to map the research trends and thematic developments in climate change adaptation to flood disasters. Data from 812 publications, spanning from 1996 to 2023, were retrieved from the Scopus database and analyzed using VOSviewer software to visualize keyword co-occurrence networks. The analysis identified five key thematic clusters: adaptation strategies and resilience (180 publications), urban planning and green infrastructure (150 publications), flood risk management (85 publications), early warning systems (60 publications), and socio-economic impacts such as health and displacement (100 publications). Over time, research output has significantly increased, particularly after 2015, with publications peaking at 150 in 2023. Regionally, Asia leads the research output with 200 publications, followed by Europe (180 publications) and North America (120 publications). The findings highlight a shift toward sustainable, nature-based solutions and the integration of advanced technologies such as machine learning in flood management. The increasing focus on the socio-economic dimensions of flood adaptation, particularly in vulnerable communities, underscores the need for more inclusive approaches. Future research should prioritize underrepresented regions, such as Africa and Latin America, and foster interdisciplinary collaboration to address the complex challenges of climate-induced floods.